PRECISION AND INDEPENDENCE IN SCIENCE AND ENVIRONMENTAL JOURNALISM - Rodrigues, Allan Soljenítsin Barreto; Barbosa, Danilo Egle Santos; da Silva, Edilene Mafra; Bandeira, Thalita Lima (Seven Editora, 2026)
The problems associated with environmental degradation have been intensifying and generating impacts on a global scale, reinforcing the need for society to have access to clear, reliable, and socially relevant information. In this scenario, the media assumes a strategic role in public awareness of environmental and scientific issues. This article analyzes the journalistic coverage of science and the environment carried out by the online version of a weekly magazine with national circulation, with an emphasis on the approach to scientific knowledge related to the Amazon. The research is the result of the work of researchers from the Research Group on Communication, Culture and Amazonia (Trokano). Reports published between January 2010 and January 2020 were examined, and the data were analyzed using qualitative and quantitative procedures, considering the categories of analysis: accuracy, independence, contextualization, plurality, and awareness. This work specifically presents the results related to the categories of accuracy and independence, highlighting positive performance in the evaluated criteria. The results indicate that the scientific and environmental content was disseminated with informative quality, contributing to a greater understanding among readers and facilitating decision-making processes related to the topics covered.